2006
DOI: 10.1007/s00432-006-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased C-MYC copy numbers on the background of CDKN2A loss is associated with improved survival in nodular melanoma

Abstract: We conclude that the C-MYC increased copy number changes on the background of CDKN2A deletions seem to be related to a low metastatic potential and better patients' outcome in primary NMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In our study, MYC copy number gain was distributed throughout all RCM CM types while CDKN2A homozygous deletion was identified in RCM CM types 3 and 4, conventionally associated with the nodular CM subtype, the most rapidly growing and aggressive variant of CM . This finding of combined MYC gain and CDKN2A deletion in RCM CM types 3 and 4 could indicate that the accumulation of consecutive genetic aberrations may lead to a more invasive phenotype, tumor progression and invasion . As previously suggested, our data might confirm that MYC and CDKN2A aberrations contribute to the development of the invasive potential of the primary tumor rather than to the metastatic process …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, MYC copy number gain was distributed throughout all RCM CM types while CDKN2A homozygous deletion was identified in RCM CM types 3 and 4, conventionally associated with the nodular CM subtype, the most rapidly growing and aggressive variant of CM . This finding of combined MYC gain and CDKN2A deletion in RCM CM types 3 and 4 could indicate that the accumulation of consecutive genetic aberrations may lead to a more invasive phenotype, tumor progression and invasion . As previously suggested, our data might confirm that MYC and CDKN2A aberrations contribute to the development of the invasive potential of the primary tumor rather than to the metastatic process …”
Section: Discussionsupporting
confidence: 87%
“…Several studies have investigated the prognostic significance of MYC and CDKN2A aberrations in patients with CM . In the nodular subtype, Koynova et al observed that combined MYC gain and CDKN2A deletion were detected exclusively in tumors >1.1 mm in thickness. In our study, MYC copy number gain was distributed throughout all RCM CM types while CDKN2A homozygous deletion was identified in RCM CM types 3 and 4, conventionally associated with the nodular CM subtype, the most rapidly growing and aggressive variant of CM .…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative genomic hybridization studies provide evidence for overrepresentation of the long arm of chromosome 20 in malignant melanoma. These studies also suggest that chromosome 20q contains genes that may contribute to melanoma pathogenesis [28,29]. However, the specific genes that are highly expressed due to DNA amplification of chromosome 20q are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of 9p21.3, which includes CDKN2A and CDKN2B genes, is associated with poor prognosis [80]. Moreover, CDKN2A deletions combined with C-MYC increased copy number changes seem to be related to a low metastatic potential and better patient outcomes in primary nodular melanoma [81]. Although gene CDKN2A is predominantly deleted, rare amplification can occur [66].…”
Section: Familial Melanomamentioning
confidence: 99%